FIDO2 Protocol and Biometric Security. - Sultonov Sarvar Mahammadodilovich (Periodica Journal, 2023)
The FIDO2 protocol is a cybersecurity protocol designed for user identification and authentication, developed by the FIDO (Fast Identity Online) Alliance. It includes the FIDO U2F (Universal Second Factor) and UAF (Universal Authentication Framework) protocols and aims to make identification and authentication processes on websites, web services or other processes simple, secure, and efficient
Keywords: FIDO2; U2F; WebAuthn